# Solve the following by elimination method: 2x - 3y = 5 3x - (2y-3)/5 = 4

beckden | Certified Educator

calendarEducator since 2011

starTop subjects are Math, Science, and Business

(1) 2x-3y=5
(2) 3x-(2y-3)/5=4

Simplify (2)
(5)3x - (5)(2y-3)/5 = 4(5)
15x - 2y + 3 = 20
(3) 15x - 2y = 17

2x - 3y = 5 multiply by -2 to get -4x + 6y = -10   (4)
15x - 2y = 23 multiply by 3 to get 45x - 6y = 51   (5)

Now add (4) and (5) to get

41x = 41  and solving for x we get

x = 1

To find y we substitute x = 1 into (1) and solve for y
2(1)-3y=5

3y = 2 - 5
3y = -3
y = -1

Check the answers in the 2nd equation
3x-(2y-3)/5=4
3(1) - (2(-1)-3)/5 = 4
3 - (-5)/5 = 4
3 - (-1) = 4
4 = 4  Checks...

So our answer is (1, -1)

check Approved by eNotes Editorial

Tushar Chandra | Certified Educator

calendarEducator since 2010

starTop subjects are Math, Science, and Business

We have to solve by elimination the set of equations:

2x - 3y = 5 ...(1)

3x - (2y-3)/5 = 4 ...(2)

3*(1) - 2*(2)

=> 6x - 9y - 6x + 2*(2y-3)/5 = 15 - 8

=> -9y + (2/5)(2y - 3) = 7

=> -45y + 4y - 6 = 35

=> -41y = 41

=> y = -1

(2)

=> 15x - 2y + 3 = 20

=> 15x - 2y = 17 ...(3)

2*(1) - 3*(3)

=> 4x - 6y - 45x + 6y = 10 - 51

=> -41x = -41

=> x = 1

The solution is x = 1 and y = -1

check Approved by eNotes Editorial

ajoydasprodip | Student

2x - 3y = 5 ---------------(i)

3x - (2y-3)/5 = 4 -------(ii)

From eqn ---( i )

3y = 2x-5

## => y =(2x-5)/3 ---- (iii)

=>2y = (4x-10)/3

=>2y - 3 = (4x - 10)/3 - 3

=  (4x -10- 9)/3

= ( 4x -19 )/3

## 3x - (2y-3)/5 = 4

Now, 3x - (4x - 19 )/15 = 4

=> 45x - 4x +19 = 60

=> 41x= 41

=> x= 1

From eqn ---(iii)

y= (2*1 - 5 )/3

= -3/3 = - 1

(x,y) = (1, -1) -------- solutiom.

check Approved by eNotes Editorial